2021
DOI: 10.3390/pharmaceutics13122015
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotide-Based Therapy of Viral Infections

Abstract: Nucleic acid-based therapeutics have demonstrated their efficacy in the treatment of various diseases and vaccine development. Antisense oligonucleotide (ASO) technology exploits a single-strand short oligonucleotide to either cause target RNA degradation or sterically block the binding of cellular factors or machineries to the target RNA. Chemical modification or bioconjugation of ASOs can enhance both its pharmacokinetic and pharmacodynamic performance, and it enables customization for a specific clinical pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 141 publications
(180 reference statements)
0
27
0
Order By: Relevance
“…The development of such technology is especially important, as more and more drug-resistant influenza strains evolved with time [ 58 ]. Different RNA-based nucleic acid therapies have been proposed in the case of RNA viruses [ 59 ]. Depending on the mechanism of the inhibition, these can block the replication processes of the virus by creating steric blockades or lead to RNase H cleavage of targeted RNA [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of such technology is especially important, as more and more drug-resistant influenza strains evolved with time [ 58 ]. Different RNA-based nucleic acid therapies have been proposed in the case of RNA viruses [ 59 ]. Depending on the mechanism of the inhibition, these can block the replication processes of the virus by creating steric blockades or lead to RNase H cleavage of targeted RNA [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting conserved RNA structures and sequences of SARS-CoV-2 is an alternative approach to inhibiting viral infection and progression ( 209 , 210 ). The most well-known examples are antisense oligonucleotides (ASOs), which contain modifications at their positions, such as 2-O-methyl (2-OME), 2-O-methoxy (2-MOE), locked nucleic acid (LNA), morpholino, or other nucleotide modifications, which may increase RNA base pairing, metabolic stability, and/or delivery ( 209 , 211 , 212 ). Circular RNAs (circRNAs) can also be engineered as antisense RNAs to disrupt SARS-CoV-2 genome expression and viral proliferation ( 213 ).…”
Section: Translational Strategies Against Sars-cov-2mentioning
confidence: 99%
“…These antisense-RNAs form stable hybrids with their target RNAs, which cause target RNAs cleavage/degradation or block mRNA processing or translation ( 213 215 ). Antisense DNA oligonucleotide forms a hybrid with the target RNA and induces cleavage of RNA by RNase H, an endonuclease that cleaves the RNA-DNA strands, limiting the synthesis of the encoded protein ( 212 ). Another study showed that in a pseudovirus infection model, 2’-OME/SP-ASO conjugated with four 2’-5’-oligonucleotides that can induce RNase L-mediated cleavage and degradation of SARS-CoV-2 envelope and spike, thereby effectively inhibiting the spread of the virus ( 216 ).…”
Section: Translational Strategies Against Sars-cov-2mentioning
confidence: 99%
“…It is also possible to target ITAFs with specific ASOs that inhibit ITAF expression and, hence, modulate IRES activity depending on the effect of the ITAF on the regulated IRES—activator ITAF ( Figure 2 B) or inhibitory ITAF ( Figure 2 C). Several ASOs have already been designed to target cellular host factors needed to regulate IRES-mediated translation upon viral infection (reviewed in [ 125 ]). However, this approach could be more complex and less accurate since each ITAF can regulate more than one IRES simultaneously, creating a general effect on several pathways, instead of mediating a specific and desired interaction and/or IRES [ 114 ].…”
Section: Rna-based Therapies To Modulate Translation Initiation Dysre...mentioning
confidence: 99%